PENINGKATAN NILAI TAMBAH DAN PENGOLAHAN KOPI ROBUSTA (Robusta Canephora) DI DESA AWANG BANGKAL BARAT KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN (PEMBERDAYAAN KELOMPOK TANI –TANI BERSAMA) - Fitri Mahyudi; Husinsyah; Yarna Hasiani (Fakultas Pertanian UVAYA Banjarmasin, 2026)
Awang Bangkal Barat Village, which is located in Karang Intan District, has long been known as one of the kopi producing areas, especially the kopi Robusta type in the southern region of Banjar Regency, South Kalimantan Province. It cannot be denied that the focus of kopi plant utilization activities is not only related to increasing the productivity (volume) of results, but also increasing the quality of the kopi produced. This is a factor that cannot be ignored, because product quality is the main reference for customers in determining the choice of variants spread on the market. This means that quantity and quality are two things that cannot be separated, on the one hand the volume of harvest must be able to maintain the stability of product needs, but on the other hand, product quality must not be neglected just because of pursuing the volume of market demand. Therefore, this service activity is focused on efforts to improve post-harvest quality based on processing kopi into goods that can have economic and tourism value. Bearing in mind, until now the Kopi farmer group in this area still uses manual methods which makes the process longer and quite tiring and has an impact on product quality. This has been accompanied by a transfer of technology to the Kopi Robusta farmer group in the service area. The method used is as follows: (a). Counseling on strategies for improving the quality of kopi kopi Robusta commodities; (b). Training on transfer of technology for the use of kopi plants; and (c) Discussion of the evaluation of the results of the counseling and training that has been carried out as recommendation material for community service activities in the following year.